The effects of transformational leadership dimensions on employee performance in the hospitality industry in Malaysia - Teoh, Brenda Ern Wei; Wider, Walton; Saad, Abidah; Sam, Toong Hai; Vasudevan, Asokan; Lajuma, Surianti (Frontiers in Psychology, 2022)
Employee performance plays a crucial role in the productivity of organizations, especially in the hospitality industry in Malaysia. This work performance is influenced by leadership style, and finding the type of leadership style that is suitable to apply to employees is crucial, especially while in the midst of the COVID-19 pandemic. Transformational leadership theory is selected for this study in determining leadership styles. There are four dimensions under transformational leadership theory, namely idealized influence, individualized consideration, inspirational motivation and intellectual stimulation. Data were collected online from 400 employees working in the hospitality industry in Malaysia and analyzed using partial least square structure equation modeling (PLS-SEM). The findings show that only two dimensions of transformational leadership, namely idealized influence and inspirational motivation, have a significant positive influence on employee performance. Implications in the context of human resource management and recommendations to increase employee performance are also dis-cussed.